2017
DOI: 10.1097/qco.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated neurocognitive disorder

Abstract: Purpose of review HIV associated neurocognitive disease (HAND) is the most active topic for neuroAIDS investigations at present. Although impairment is mild in patients successfully treated with modern antiviral regimens, it remains an ongoing problem for HIV patients. It is important to update the emerging research concerning HAND. Recent findings The virus enters the brain during acute infection, with evidence for abnormal functioning that may occur early and often persists. Direct relationships with ongoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 72 publications
(65 reference statements)
1
75
0
1
Order By: Relevance
“…We observed that in all our patients diagnosed with cognitive impairment the MRI findings were similar to those described in the literature in patients with HIV infection (cortical and subcortical atrophy, ventricular enlargement, confluent signal abnormalities within the deep white matter) [9,45]. Some authors reported volumetric changes in the cortical areas, basal ganglia and white matter in HIV-infected patients at different stages of their disease: these changes were more severe in most advanced stages but were evident even in asymptomatic individuals [46].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We observed that in all our patients diagnosed with cognitive impairment the MRI findings were similar to those described in the literature in patients with HIV infection (cortical and subcortical atrophy, ventricular enlargement, confluent signal abnormalities within the deep white matter) [9,45]. Some authors reported volumetric changes in the cortical areas, basal ganglia and white matter in HIV-infected patients at different stages of their disease: these changes were more severe in most advanced stages but were evident even in asymptomatic individuals [46].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, there is no agreement in the literature about the best tools that must be used to identify such patients in terms of neuropsychological tests and of CSF or blood biomarkers and neuroimaging characteristics [9,37]. In the HAART era, the use of neuropsychometric performance testing is more challenging since the major aim is to identify patients with more subtle deficits [9]. Frequently used methods include versions of the Mini-mental Status Exam, the Montreal Cognitive Assessment, the composite Z scores of several brief neuropsychometric tests used in the AIDS Clinical Trials Group system, the International HIV dementia screen, and parts of CogState devices.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Combination antiretroviral therapy (cART) can improve cognitive performance and brain metabolism in some patients with HAND 2, 5, 6 . However, many antiretroviral drugs do not penetrate well into the central nervous system 7 , and neurocognitive deficits are reversed in many but not all patients 8, 9 . The prevalence of HAND in HIV positive (HIV+) individuals with advanced infection remains around 45-50%, and patients are now surviving for years with HIV infection and HAND as chronic conditions 10, 11 .…”
Section: Introductionmentioning
confidence: 99%